2015
DOI: 10.1186/s13071-015-1147-0
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis in the central provinces of Hama and Edlib in Syria: Vector identification and parasite typing

Abstract: BackgroundCutaneous leishmaniasis is a disease transmitted by sand fly bites. This disease is highly prevalent in Syria where Leishmania major and Leishmania tropica are the known aetiological agents. In 2011, more than 58,000 cases were reported in the country by the Ministry of Health. The central region of the country harbors 20 % of the reported cases. However, the epidemiology of the disease in this area is not well understood. An epidemiological survey was conducted in 2010 to identity the circulating pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…L. infantum and L. donovani , which are considered classical pathogens for VL, were repeatedly confirmed in skin lesions of patients participating in this survey. In Syria, L. infantum has been reported previously as a causative agent of CL in humans ( 21 ); however, L. donovani had previously been isolated only from sand flies ( 23 ). Further, L. donovani has repeatedly been found in the neighboring countries Cyprus, Turkey, Iraq, and Israel ( 24 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…L. infantum and L. donovani , which are considered classical pathogens for VL, were repeatedly confirmed in skin lesions of patients participating in this survey. In Syria, L. infantum has been reported previously as a causative agent of CL in humans ( 21 ); however, L. donovani had previously been isolated only from sand flies ( 23 ). Further, L. donovani has repeatedly been found in the neighboring countries Cyprus, Turkey, Iraq, and Israel ( 24 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, civil war in Syria led massive displacement of people. Therefore, the number of cutaneous leishmaniasis cases increased significantly in neighbouring countries like Turkey, Jordan and Lebanon [3]. Alawieh et al reported that 96.6% of the all new cases in Lebanon in 2013 occured among Syrian refugees [4].…”
Section: Letter To the Editormentioning
confidence: 99%
“…Cutaneous leishmaniasis is endemic in Syria and increased incidence of the disease has been reported between 1997 and 2011 [3]. Recently, civil war in Syria led massive displacement of people.…”
Section: Letter To the Editormentioning
confidence: 99%
“…However, in early 2013, an alarming increase to 41,000 cutaneous leishmaniasis cases was reported ( 3 , 4 ). The regions most affected are under Islamic State control; 6,500 cases occurred in Ar-Raqqah, Diyar Al-Zour, and Hasakah.…”
mentioning
confidence: 99%
“…papatasi and Ph. sergenti sand fly populations exist in Syria and Iraq ( 4 ). The presence of these vectors in regions of instability can create new cutaneous leishmaniasis foci, which might have debilitating, and often stigmatizing, consequences for residents and deployed military personnel ( 10 ).…”
mentioning
confidence: 99%